Digitalisasi Manajemen Pendidikan Islam: Strategi Inovatif untuk Meningkatkan Mutu Lembaga - Yustizar; Yusuf Hadijaya (Program Studi Pendidikan Agama Islam, 2025)
ABSTRACT This study aims to explore the integration of Islamic education management with digital technology to enhance the quality of Islamic educational institutions. The issue raised in this research is the challenge of implementing technology in Islamic educational institutions, particularly in improving teaching and institutional quality, while maintaining a balance between Islamic principles and technological advancement. The method used in this study is a literature review and content analysis with a descriptive qualitative approach. The results of the study indicate that the integration of digital technology can enrich academic, moral, and spiritual aspects of Islamic education. However, challenges such as low digital literacy and infrastructure disparities still hinder the optimal implementation of technology. This research also highlights the importance of visionary leadership in managing technology and human resources in Islamic educational institutions. Overall, this study contributes to the development of technology-based learning strategies that remain grounded in Islamic values to create a modern, intelligent, and character-driven generation.